Study on coagulation profiles and platelet function in trauma-induced coagulopathy caused by three types of injury. Issue 6 (June 2020) - Huang, Sunhua; Tang, Yao; Lin, Wenhao; Wen, Ke; Han, Wei; Lin, Zhexuan; Han, Ming
Highlights: It might be the failure of forming a strong clot instead of the prolonged clot time, which contributed to traumatic coagulopathy. The loss of platelets might be the main reason for HS-induced coagulopathy. AA-dependent pathway inhibition might account for MI-induced coagulopathy. ADP-dependent pathway inhibition might be the major contributor for TBI-induced coagulopathy. Abstract: Background: Traumatic coagulopathy is a major public health issue globally with undefined mechanisms. We established rat models of hemorrhagic shock (HS), multiple injury (MI) and traumatic brain injury (TBI) to investigate the diversity of traumatic coagulopathy, especially platelet dysfunction. Methods: Seventy male SD rats were divided randomly into seven groups( n  = 10): control, HS30min, HS3h, MI30min, MI3h, TBI30min and TBI3h . Plasma or whole blood was collected for conventional coagulation tests, thromboelastography and platelet mapping. X-ray, 7T magnetic resonance imaging and hematoxylin-eosin staining of injured tissues were conducted to confirm the injuries of rats model. Results: The activated partial thromboplastin time (aPTT) prolonged significantly in HS30min and MI3h groups, compared with those in control ( P  = 0.0403 and P  = 0.0076, respectively). R values decreased in HS30min and HS3h groups, compared with those in control ( P  < 0.0001 and P  < 0.0001, respectively). The maximum amplitude (MA) were 71.8 ± 0.6 mm, 71.9 ± 0.5 mm, 71.8 ± 0.7 mm, 70.0 ± 0.7 mm, 72.6 ± 0.9 mm, 70.4 ± 0.9 mm in HS30min, HS3h, MI30min, MI3h, TBI30min and TBI3h groups respectively, which were lower than those in control ( P  = 0.0304, P  = 0.0205, P  = 0.0431, P  = 0.0007 and P  = 0.0066, respectively). The platelet counts were 539±46 × 10 9 /L, 523±31 × 10 9 /L, 629 ± 18 × 10 9 /L and 636±20 × 10 9 /L in HS30min, HS3h, MI3h and TBI3h groups respectively, which were lower than those in control ( P  = 0.0040, P  = 0.0001, P  = 0.0127 and P  = 0.0232, respectively). The adenosine diphosphate (ADP) inhibition rate decreased in HS30min group, compared with that in control ( P  = 0.0355). While, ADP inhibition rate increased in HS3h and TBI3h groups ( P  = 0.0041 and P  = 0.0433 vs. control, respectively). The arachidonic acid (AA) inhibition rate increased in MI30min and MI3h groups, compared with control ( P  = 0.0029 and P  = 0.0185, respectively). Conclusion: These results demonstrated that it might be the failure of forming a strong clot instead of the prolonged clot time, which contributed to traumatic coagulopathy. The platelet dysfunctions might contribute to trauma-induced coagulopathy in different ways. The loss of platelets might be the main reason for HS-induced coagulopathy. While, AA-dependent pathway inhibition might account for MI-induced coagulopathy. ADP-dependent pathway inhibition might be the major contributor for TBI-induced coagulopathy.